2013
DOI: 10.1097/ccm.0b013e31827ca4e1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Hospital Discharge in ICU Patients*

Abstract: In-hospital mortality underestimates the true mortality of ICU patients as the mortality in the first months after hospital discharge is substantial. Most ICU patients still have an increased mortality risk in the subsequent years after hospital discharge compared with the general Dutch population. The mortality after hospital discharge differs widely between ICU subgroups. Future studies should focus on the analysis of mortality after hospital discharge that is attributable to the former ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 23 publications
11
74
2
3
Order By: Relevance
“…Previous comparisons between ICU patients in general and sepsis patients in particular have shown a higher post-ICU mortality risk than in the general public (79)(80)(81)96), and a higher risk of death post-ICU in sepsis patients in than in other patient categories (83,98,100). However, it is unclear to what extent this increased risk of death is related to sepsis itself, or to the severity of illness during the acute phase, irrespective of the underlying cause.…”
Section: On Predicting Cardiac Outcome In Icu Patients (Papers I -Iv)mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous comparisons between ICU patients in general and sepsis patients in particular have shown a higher post-ICU mortality risk than in the general public (79)(80)(81)96), and a higher risk of death post-ICU in sepsis patients in than in other patient categories (83,98,100). However, it is unclear to what extent this increased risk of death is related to sepsis itself, or to the severity of illness during the acute phase, irrespective of the underlying cause.…”
Section: On Predicting Cardiac Outcome In Icu Patients (Papers I -Iv)mentioning
confidence: 99%
“…However, as many as one-third of ICU patients may still be in hospital at 30 days, and a substantial proportion of deaths occur soon after hospital discharge (83,84). There are also indications of an increasing number of ICU patients being discharged from hospital not to home, but to other care facilities (5).…”
Section: Icu Outcome and Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…A large proportion of patients nursed in a general intensive care unit die within the first months after discharge, 52 and it has been shown that these patients have decreased survival compared with that of the general population. 53 Several factors indicate that there can be differences in longterm survival of patients after burns when compared with that of patients nursed in general intensive care. 54,55 Patients with burns are injured, not ill; they are younger than most of those in a general intensive care unit, and their pre-existing medical conditions differ.…”
Section: Long-term Survivalmentioning
confidence: 99%